2000
DOI: 10.2169/internalmedicine.39.979
|View full text |Cite
|
Sign up to set email alerts
|

Type II Diabetes Mellitus and Primary Sjoegren's Syndrome Complicated by Pleural Effusion.

Abstract: A 73-year-old manwas admitted to our hospital because of pleural effusion and nephrotic syndrome. Sjogren's syndrome (Sjs) was diagnosed based on a positive test for antibodies to Ro and La, and the result of labial salivary gland biopsy. The pleural effusion showed a high number of lymphocytes and high titers of antibodies to Ro and La. By immunohistochemistry, it was determined that infiltrating CD3+ cells predominated over infiltrating CD20+cells in the pleura. Nephrotic syndromewasalso present, which, as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There have only been nine previous reports in the literature of pleural effusion occurring as a specific complication of primary SS (6167)(68). Pleural fluid in these cases was characterized by lymphocytosis, elevated levels of SS-A/SS-B antibodies, and low complement levels.…”
Section: Pleural Involvementmentioning
confidence: 99%
“…There have only been nine previous reports in the literature of pleural effusion occurring as a specific complication of primary SS (6167)(68). Pleural fluid in these cases was characterized by lymphocytosis, elevated levels of SS-A/SS-B antibodies, and low complement levels.…”
Section: Pleural Involvementmentioning
confidence: 99%
“…There have been 12 other case reports of primary SjS with pleural effusion, which are shown in Table (5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a previous study reported that no pleural effusion was observed in 40 cases of primary SjS, although it was observed in 2 of 26 cases (8%) of secondary SjS [2]. To our knowledge, there have been 11 reported cases of primary SjS complicated by pleuritis [3][4][5][6][7][8][9][10][11][12][13] (Table 1). Among them, only three patients developed pleural effusion during the clinical course, whereas the remaining eight were diagnosed simultaneously with primary SjS and pleural effusion.…”
Section: Discussionmentioning
confidence: 99%